Analisis Perbandingan Kualitas Hidup Pasien Gangguan Kecemasan Yang Mendapatkan Zolpidem dan Escitalopram di RSUD Goeteng Taroenadibrata Menggunakan Instrumen EQ-5D-5L - Saskia Nur Ubay; Khamdiyah Indah Kurniasih; Fauziah Fauziah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Anxiety disorders are among the most common mental health problems in society and can affect patients’ quality of life. This study provides a comparative overview of the quality of life of patients with anxiety disorders at Goeteng Taroenadibrata Regional General Hospital who received Zolpidem or Escitalopram therapy. The purpose of this study was to determine whether there was a significant difference in the quality of life between patients using Zolpidem and those using Escitalopram. This study was a descriptive quantitative study using a cross-sectional approach. The study population consisted of patients with anxiety disorders at Goeteng Taroenadibrata Regional General Hospital, with a sample of 60 patients divided into two groups based on the therapy received, namely Zolpidem (30 patients) and Escitalopram (30 patients). Quality of life was measured using the EQ-5D-5L instrument. The results showed that 53.3% of patients in the Zolpidem group were male, while 66.7% of those in the Escitalopram group were female. In terms of age, most patients were over 60 years old, both in the Zolpidem group (83.3%) and the Escitalopram group (80.0%). In addition, the majority of patients in both groups had been undergoing treatment for more than six months (66.7%), with 20 patients in each therapy group. Statistical analysis using the Mann-Whitney test showed no significant difference in the quality of life between patients receiving Zolpidem and those receiving Escitalopram, with a p-value greater than 0.05.